PENDEKATAN LAYANAN PENDIDIKAN BAGI ANAK ABK (ADHD RINGAN) - Tuzahara, Nyimas Khairani; Andriani, Opi; Nailussaaadah; Hania, Anggi Putri (Program Studi Pendidikan Vokasi Seni Kuliner, 2024)
Children with Attention Deficit Hyperactivity Disorder (ADHD) are often found in everyday life from school-aged children to teenagers, even if it is not treated immediately it will affect a person's future. Children with this disorder require special services to meet their needs in increasing their potential and increasing their abilities. The method used is a literature study relating to special services for children with ADHD. Based on the results of studies and observations that have been carried out, the service approach provided by teachers is to provide more attention and adjust learning needs to increase the potential and abilities of students with ADHD.